Epidemiological trends and age-period-cohort effects on periodontal diseases incidence across the BRICS from 1992 to 2021 - Xiaochan Wang; Yuting Xu; Xiangming Ma; Ruixing Nan; Yuhang Wu; Peiyu Cheng (BMC Oral Health)
Abstract Background Periodontal diseases are prevalent oral conditions, particularly burdensome in developing countries. This study examines global and BRICS countries’ changing trends in periodontal diseases incidence from 1992 to 2021, focusing on associations with age, period, and cohort effects. Materials and methods A cross-sectional burden of disease study was conducted. Data on the total population and periodontal diseases cases, all-age incidence rate, age-standardized incidence rate, and relative change in periodontal diseases incidence from 1992 to 2021 within BRICS were obtained from the Global Burden of Disease study (GBD) 2021. Furthermore, the Age-Period-Cohort (APC) model with an intrinsic estimator (IE) algorithm was employed to assess the effects of net drift, local drift, age, period, and cohort on the incidence rates of periodontal diseases over specific time periods. Results Globally, the new cases of periodontal diseases in 2021 were reported at 8961 thousand (95% uncertainty intervals: 7907, 10101), reflecting a 71.21% increase compared to 1992. In 2021, the age-standardized incidence rate of periodontal diseases across the BRICS countries ranged from 600.50 (95% uncertainty intervals: 481.27, 763.54) per 100,000 population in South Africa to 1268.96 (95% uncertainty intervals: 1119.16, 1409.94) per 100,000 population in India. The age distribution of periodontal diseases cases was relatively stable globally and among BRICS countries from 1992 to 2021. Countries exhibited similar age-effect patterns, with increasing risk with increasing age, and varying period and cohort effects, indicative of differential control measures and temporal incidence trends. Conclusions Brazil, India, and China experienced an increasing trend in the age-standardized incidence rates of periodontal diseases from 1992 to 2021, in contrast to the declining trends observed in the Russian Federation and South Africa. Furthermore, the APC analysis indicates the intricate dynamics of age, period, and cohort influences on periodontal diseases incidence. Distinct national trajectories, shaped by varying socioeconomic, cultural, and historical frameworks, highlight that public health initiatives must be meticulously customized to mitigate and control the periodontal diseases burden across diverse settings.